Effect of foot strike patterns and angles on the biomechanics of side-step cutting - Yi, Fan; Jianchao, Zhao; Wen, Zhu; Ke, Liu; Yantao, Lou (Frontiers in Bioengineering and Biotechnology, 2024)
Objectives: To determine how foot strike patterns and cutting angles affect lower extremity (LE) kinematics, kinetics, and muscle activity during side-step cutting. Methods: Twenty male college sport athletes participated in this research. Three-dimensional motion analysis featuring ground reaction force (GRF) and electromyography (EMG) of the dominant leg was used. LE kinematics, kinetics and EMG data parameters were obtained during a 45° and 90° side-step cutting involving rearfoot strikes (RFS) and forefoot strikes (FFS). Results: The significant foot strike pattern×angle interactions were observed for ankle eversion range of motion (ROM) at loading phase. Cutting of 90° had greater knee flexion ROM,knee valgus ROM and knee varus moment compared to 45°. RFS cutting had greater knee flexion, hip flexion, knee valgus, knee varus moment, knee varus moment and ankle eversion ROM. FFS cutting produced a lower vertical GRF, lateral GRF and a loading rate. Both vastus medialis and vastus lateralis muscle activities were remarkably greater during cutting of 90° than 45°. At the loading phase, semitendinosus, biceps femoris and lateral head of gastrocnemius muscle activities during FFS cutting were considerably greater than RFS cutting. Conclusions: FFS pattern can better protect the Anterior cruciate ligament (ACL) and improve the flexibility of athletes by increasing the plantarflexion torque of ankle. The injury risk also increases with larger cutting angle. The EMG activities of semitendinosus and biceps femoris are vital for the stability of knee joint during side-step cutting, which helps reduce ACL stress during buffering.